The labor market in Spain, 2002-2016 - Anna Sanz-de-Galdeano; Anastasia Terskaya (IZA World of Labor, 2017)
Spain, the fourth largest eurozone economy, was hit particularly hard by the Great Recession, which made its chronic labor market problems more evident. Youth and long-term unemployment escalated during the crisis and, despite the ongoing recovery, in 2016 were still at unsustainably high levels. The aggregate rate of temporary employment declined during the recession, but grew among youth. Most interesting have been the narrowing of the gender gap in labor force participation, the decline in the share of immigrants in employment and the labor force, and the overall increase in wage inequality.
Keywords: I10; I12; I13; J31; J15; J16; 330; unemployment; wage inequality; Spain